ANALISIS KUALITAS AIR PDAM UNIT TIRTA MOOLANGO POHUWATO - Husain, Irawaty Indriyani; Mahmud, Marike; Husnan, Rawiyah (Civil Engineering Scientific Journal, 2025)
ABSTRACT: Water is a basic necessity for all living beings. Poor water quality can lead to health issues. This study aims to evaluate water quality based on physical, chemical, and microbiological parameters according to quality standards, analyze factors affecting water quality, and assess the water status of the Popayato Maleo River using the Pollution Index. Samples were collected from the Popayato Maleo River (raw source), PDAM Tirta Moolango reservoir, and community water taps. Tested parameters included temperature, TDS, salinity, turbidity, pH, manganese, hardness, E. coli, and coliform. Chemical tests were conducted at LPPT UGM, while physical and microbiological tests were performed at the Regional Health Laboratory of Gorontalo. River water quality was assessed using Government Regulation No. 22 of 2021, while PDAM and tap water followed Ministry of Health Regulation No. 2 of 2023. The Pollution Index referred to MOEF Regulation No. 27 of 2021. Results showed the Popayato Maleo River met the quality standard, with a Pollution Index of 0.587. However, reservoir water failed in turbidity, salinity, and coliform, while tap water failed in turbidity, salinity, E. coli, and coliform. Contributing factors include distribution systems, environmental contamination, and inadequate treatment. Regular monitoring and system improvements are recommended.Keywords: River Water Quality; PDAM; Pollution Index ABSTRAK: Air merupakan kebutuhan dasar bagi makhluk hidup. Kualitas air yang buruk dapat menimbulkan gangguan kesehatan. Penelitian ini bertujuan mengevaluasi kualitas air berdasarkan parameter fisik, kimia, dan mikrobiologi sesuai baku mutu, menganalisis faktor-faktor yang memengaruhi kualitas air, serta menilai status mutu air Sungai Popayato Maleo menggunakan Indeks Pencemaran. Sampel diambil dari Sungai Popayato Maleo (sumber air baku), reservoir PDAM Unit Tirta Moolango, dan keran masyarakat. Parameter uji meliputi suhu, TDS, salinitas, kekeruhan, pH, mangan, kesadahan, E. coli, dan coliform. Parameter kimia dianalisis di LPPT UGM, sementara parameter fisik dan mikrobiologi di Laboratorium Kesehatan Daerah Provinsi Gorontalo. Penilaian mutu air sungai mengacu pada PP No. 22 Tahun 2021, sedangkan air PDAM dan keran masyarakat berdasarkan Permenkes No. 2 Tahun 2023. Indeks pencemaran merujuk Permen LHK No. 27 Tahun 2021. Hasil menunjukkan air Sungai Popayato Maleo memenuhi baku mutu dengan nilai Indeks Pencemaran 0,587. Namun, air di reservoir PDAM tidak memenuhi pada kekeruhan, salinitas, dan coliform. Air keran masyarakat tidak memenuhi pada kekeruhan, salinitas, E. coli, dan coliform. Faktor yang memengaruhi penurunan kualitas meliputi sistem distribusi, kontaminasi lingkungan, dan proses pengolahan. Diperlukan pemantauan berkala dan perbaikan sistem pengolahan serta distribusi air.Kata kunci: Kualitas Air Sungai; PDAM; Indeks Pencemaran